A decadal‐scale numerical model for wandering, cobble‐bedded rivers subject to disturbance - De Rego, Kathryn; Lauer, J. Wesley; Eaton, Brett; Hassan, Marwan (Earth surface processes and landforms, 2020)
Alluvial rivers are composed of self‐formed channels which are sensitive to disturbances in their flow and sediment‐supply regimes. Regime changes commonly occur over decadal and longer timescales and can be caused by anthropogenic alterations such as dam construction and removal. Advances in numerical modeling have increased our ability to explore geomorphic adjustments over long timescales; however, many models designed to be run for decades or longer assume that banks are immovable or that channel width is constant. Since river channels often respond to disturbance by adjusting their geometry, this is a significant shortcoming. To investigate the impact of long‐term sediment supply alterations on channel geometry and stability, we have adapted MAST‐1D, a reach‐scale bed evolution model, to incorporate functions for bank erosion, vegetation encroachment, and local avulsions. The model is designed for medium‐large, coarse multithreaded rivers and can be run over long (decades–centuries) timescales. Bank erosion is a function of the mobility and transport capacity for structurally‐important grains which protect the bank toe. Vegetation growth is proportional to point bar width and occurs during conditions of low shear stress. Local avulsions occur when aggradation causes channel depth to drop below a threshold. We apply the model to the Elwha River in Washington, USA with the goal of investigating if and when the river recovers from dam emplacement and removal. The Elwha was dammed for nearly 100 years, and then two dams were removed, releasing a large pulse of sediment. We have modeled the set of reaches between the two dams. Our simulations suggest that channel response to dam emplacement occurs gradually over several decades but that the channel recovers to near pre‐dam conditions within about a decade following the removal. The dams leave a lasting legacy on the floodplain, which does not completely recover, even after two centuries. © 2019 John Wiley & Sons, Ltd. Key findings: We developed a numerical model to understand the relationships between sediment supply and channel‐floodplain interactions. We applied the model to the Elwha River, on which two dams were constructed in the early 20th century then removed in the 2010s. The simulations suggest that the Elwha responded to dam emplacement over several decades but recovered within several years following dam removal. The channel returned to pre‐dam conditions, but the dams left a legacy on the floodplain.